Teaching L2 pragmatics: The effects of different types of task implementation vs a PPP framework - Róg, Tomasz (Neofilolog, 2024)
The present study investigates the effect of different types of task implementation on teaching L2 interactional sequences. 81 EFL learners were randomly assigned to one of three experimental groups. In the first experimental group (T1-EG, n = 27), implicit instruction appeared during the pre-task phase, while the post-task phase included an explicit focus on forms. The second group (T2-EG, n = 32) received implicit instruction in the target structures and a reactive focus on form during task performance. The third group (PPP-EG, n = 27) followed a presentation – practice – production (PPP) lesson framework. Groups’ pragmatic production was measured using written discourse completion tasks. Results showed that in the current study, all three groups reported gains, yet the implicit-explicit condition (T1-EG) appeared to be more beneficial for teaching the interactional sequences than the implicit-only (T2-EG) or the PPP (PPP-EG) framework.